Peran Pemerintah Daerah dalam Memperkuat Pendidikan Agama melalui Kebijakan SPP Gratis di Era Otonomi (International Forum of Researchers and Lecturers, 2025)
This study examines the role of local governments in strengthening religious education through the policy of exempting Education Development Contributions (SPP) in the era of regional autonomy. The free tuition policy is one of the local government's strategic efforts to increase access and equity in religious education, especially for the underprivileged. Using a qualitative approach, this study analyzes policy implementation, obstacles faced, and the impact of policies on the quality and equity of religious education in religious education units. The results of the study show that local governments play the role of regulators and facilitators by providing supportive budgets and regulations, thereby encouraging an increase in student participation and the quality of religious education. However, challenges in data validation and budget management still need to be overcome for more optimal policy effectiveness. This study emphasizes the importance of synergy between local governments and communities in developing inclusive and sustainable religious education in the era of decentralization.